Floating Exchange Rates in Developing Countries : Experience with Auction and Interbank Markets - Huh, Kyong; Christensen, Benedicte; Quirk, Peter; Sasaki, Toshihiko (Washington, D.C. : International Monetary Fund, 1987)
In recent years, an increasing number of developing countries have adopted market-determined floating exchange rates. This development has represented a significant step forward in the evolution toward exchange rate flexibility that has taken place in the developing country group since the adoption of generalized floating by industrial countries in 1973.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet